Genghis Khan life, death, and resurrection - Man, John. (London Bantam, 2011)
Genghis Khan - creator of the greatest empire the world has ever seen - is one of history's immortals. In Central Asia, they still use his name to frighten children. In China, he is honoured as the founder of a dynasty. In Mongolia he is the father of the nation. In the USA, Time magazine, voted Genghis Khan 'the most important person of the last millennium'. But how much do we really know about this man? How is it that an unlettered, unsophisticated warrior-nomad came to have such a profound effect on world politics that his influence can still be felt some 800 years later?
Includes bibliographical references (p. 374-378) and index.
Keywords: Genghis Khan, 1162-1227.